Safety and Diagnostic Accuracy of Dobutamine Stress Echocardiography - Shah, Ram Kishor (Nepalese Heart Journal, 2017)
Exercise and pharmacologic stress echocardiography has been used routinely in clinical practice for the past twenty to thirty years. Dobutamine stress echocardiography (DSE) is well established as a safe, feasible, and accurate modality for detection of myocardial ischemia and prognostication in patients with known or suspected coronary artery disease, particularly when they have limited exercise capacity. Serious side effects during or shortly after DSE are uncommon, with ventricular fibrillation or myocardial infarction occurring in approximately 1 of 2,000 studies. No deaths have been reported. On the basis of a total number of 2,246 patients, reported in 28 studies, the sensitivity, specificity and accuracy of the test for the detection of coronary artery disease (CAD) were 80%, 84% and 81%, respectively. Mean sensitivities for one, two and three-vessel disease were 74%, 86% and 92%, respectively. The sensitivity of detection of disease in the let circumflex coronary artery (55%) was lower, both compared with that for left anterior descending (72%) and right coronary artery disease (76%). The sensitivity of predicting multivessel disease by multiregional echocardiographic abnormalities varied widely, from 8% to 71%. In direct comparisons, DSE was superior to exercise electrocardiography and dipyridamole echocardiography and comparable to exercise echocardiography and radionuclide imaging. DSE is useful, feasible and safe exercise independent stress modality for assessing the presence, localization and extent of CAD.